2016
DOI: 10.2147/hmer.s79243
|View full text |Cite
|
Sign up to set email alerts
|

Defibrotide in the treatment of hepatic veno-occlusive disease

Abstract: Hepatic veno-occlusive disease (VOD), also known as sinusoidal obstruction syndrome (SOS), represents the most frequent complication in patients in early phase following hematopoietic stem-cell transplantation (HSCT). In its severe form, VOD/SOS can be associated with multiorgan failure and with a mortality rate >80% by day +100. Defibrotide (DF) (a mixture of 90% single-stranded phosphodiester oligonucleotides and 10% double-stranded phosphodiester oligonucleotides derived from controlled depolarization of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Progress in oligonucleotide chemistry helped to establish RNA compositions and sequence designs that are stable and efficient with lasting therapeutic effects. RNA therapies, approved or in clinical trials, which use one or more of the first generation modifications ( Fig 4 – Gen1), they can be classified as a foundational technology, and products primarily using sugar and backbone modifications as first-generation RNA therapeutics ( Figure 4 – ‘Gen.1’), they often need to be delivered in relatively high doses of up to 60 mg/kg of body weight [ 27 ] which impacts production costs of such RNAs or RNA analogues, turning some therapies prohibitively expensive. However, major advances in large scale production of shorter RNAs has reduced the production cost aspect considerably and the major driving forces for development of higher efficacy RNA therapeutics is to reduce off-target effects and more generally to improve the toxicity and safety profile.…”
Section: Challenges In Developing Successful Rna Therapymentioning
confidence: 99%
“…Progress in oligonucleotide chemistry helped to establish RNA compositions and sequence designs that are stable and efficient with lasting therapeutic effects. RNA therapies, approved or in clinical trials, which use one or more of the first generation modifications ( Fig 4 – Gen1), they can be classified as a foundational technology, and products primarily using sugar and backbone modifications as first-generation RNA therapeutics ( Figure 4 – ‘Gen.1’), they often need to be delivered in relatively high doses of up to 60 mg/kg of body weight [ 27 ] which impacts production costs of such RNAs or RNA analogues, turning some therapies prohibitively expensive. However, major advances in large scale production of shorter RNAs has reduced the production cost aspect considerably and the major driving forces for development of higher efficacy RNA therapeutics is to reduce off-target effects and more generally to improve the toxicity and safety profile.…”
Section: Challenges In Developing Successful Rna Therapymentioning
confidence: 99%
“…PA and its hydrolysis products are not toxic, but when they reach the liver, they are deoxygenated by cytochrome P450 enzyme (CYP) 3A to form pyrrole-like derivatives. This metabolite binds to DNA/RNA in hepatocytes, thus affecting protein synthesis and inhibiting cell division, which in turn causes severe damage to the liver [21].…”
Section: Consumption Of Plants Containing Pyrrolidine Alkaloids (Pa)mentioning
confidence: 99%
“…In addition to the above two common types, it has also been reported that SOS is associated with chemotherapy and radiotherapy for solid tumors, such as chemotherapy with cyclophosphamide. Common SOS-related drugs are cyclophosphamide, busulfan, dacarbazine, 6-mercaptopurine, 6-thioguanine, dacarbazine, actinomycin D, gemtuzumab, melphalan, oxaliplatin, cytarabine, and uratan [21].…”
Section: After Radiation and Chemotherapymentioning
confidence: 99%